Cultural Contributions of Prominent Families in Western Sudan (Journal of human and social sciences, 2015)
This research aims to highlight the cultural and scientific contributions of the Ahl Andagh Muhammad family in the Western Sudan region from the 9th to the 11th century AH. It examines the family's role in judiciary, preaching, education, authorship, and the establishment of libraries, and how they contributed to preserving the Arab-Islamic identity in the region.